1980
DOI: 10.7326/0003-4819-92-5-609
|View full text |Cite
|
Sign up to set email alerts
|

Continuous Ambulatory Peritoneal Dialysis: Three-Year Experience at One Center

Abstract: Three years of clinical experience with continuous ambulatory peritoneal dialysis are summarized. Serum urea nitrogen, creatinine, hematocrit, nerve conduction velocity, calcium, inorganic phosphorus, serum proteins, and electrolytes have been maintained in acceptable ranges. Peritonitis, although reduced in incidence because of solutions in plastic bags and a new adapter, is still a problem. Excessive carbohydrate absorption, obesity, and high serum triglyceride concentrations may be long-term problems in som… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
39
1
1

Year Published

1981
1981
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 175 publications
(43 citation statements)
references
References 5 publications
2
39
1
1
Order By: Relevance
“…However, the higher serum bicarbonate levels in CAPD patients indicate better control of the acidosis and this may have a good impact on the renal osteodystrophy, as was demonstrated by Gokal et al 8 There was no statistically significant difference in the mean hemoglobin value for the two groups. This is similar to what some observers have found, 9,10 but others 11,12 have reported a 5 to 7% increase in the average hematocrit readings at one year in patients initiated and maintained on CAPD. The reason for this increased hemoglobin concentration is not known, but it could be due to better fluid control or bone marrow responsiveness to erythropoietin.…”
Section: Discussionsupporting
confidence: 78%
“…However, the higher serum bicarbonate levels in CAPD patients indicate better control of the acidosis and this may have a good impact on the renal osteodystrophy, as was demonstrated by Gokal et al 8 There was no statistically significant difference in the mean hemoglobin value for the two groups. This is similar to what some observers have found, 9,10 but others 11,12 have reported a 5 to 7% increase in the average hematocrit readings at one year in patients initiated and maintained on CAPD. The reason for this increased hemoglobin concentration is not known, but it could be due to better fluid control or bone marrow responsiveness to erythropoietin.…”
Section: Discussionsupporting
confidence: 78%
“…[3] Nolph et al reported that protein loss in the continuous ambulatory peritoneal dialysis (CAPD) dialysate may be up to 15 g/day, and patients are required to ingest high-protein diets. [4] The development of amino acid solutions in the 1950s led to their use in patients with impossible or inadequate ingestion. Recently, some patho-specific amino acid solutions for renal failure were developed to study amino acid metabolism.…”
Section: Introductionmentioning
confidence: 99%
“…Since the introduction of continuous ambulatory PD, studies have explored the question of whether dialysis modality per se independently affects patient outcomes, including an early attempt at a randomized, controlled trial (5)(6)(7). In this review, we present our analysis of the current state of knowledge about the effects of dialysis modality on patient outcomes in context of the declining proportion of patients who undergo PD in many parts of the world.…”
mentioning
confidence: 99%